Ability Drain: Size, Impact, and Comparison with Brain Drain under Alternative Immigration Policies - Maurice Schiff (Global Labor Organization (GLO), 2017)
Ability drain's (AD) impact seems economically significant, with 30% of US Nobel laureates since 1906 being immigrants, and immigrants or their children founding 40% of Fortune 500 companies. Nonetheless, while brain drain (BD) and gain (BG) have been studied extensively, AD has not. I examine migration's impact on ability (a), education (h), and productive human capital or 'skill' s=s(a,h), for source country residents and migrants under a) the points system (PS) which accounts for h, and b) the 'vetting' system (VS) which accounts for s (e.g., US H-1B program). Findings are: i) Migration reduces (raises) residents' (migrants') average ability, with an ambiguous (positive) impact on average education and skill, and net skill drain, SD, likelier than net BD; ii) these effects increase with ability's inequality or variance, are greater under VS than PS, and hurt source countries; iii) the model and two empirical studies suggest that, for educated US immigrants, average AD ≥ BD, with real income about twice home country income; iv) SD holds for any BD, and also for a very small AD (7.4% of our estimate). Policy implications are provided.
Keywords: F22; J24; J61; O15; 330; Migration; points system; vetting system; ability drain; brain drain; brain gain